ANALISIS INTERAKSI OBAT PADA PASIEN DISPEPSIA DENGAN PENYAKIT PENYERTA DI INSTALASI RAWAT INAP DI RUMAH SAKIT X KABUPATEN MAJALENGKA TAHUN 2024 - Yulianti, Tia; Ade Irawan; Putra, Teguh Adiyas (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2025)
Dyspepsia is common digestive disorder that can significantly impact a patient's quality of life, particularly in individuals with comorbid conditions. Lifestyle factors, stress, and the use of various medications can contribute the onset of symptoms. One important aspect to consider is drug interactions, especially in elderly patients undergoing polypharmacy. This study aims to analyze drug usage patterns and identify potential drug interactions in patients diagnosed with dyspepsia and comorbidities. The research employed a non-experimental observational design using a retrospective descriptive method. Data were collected from inpatient medical records at Hospital X in Majalengka Regency, involving patients diagnosed with dyspepsia and accompanying illnesses. The profile dyspepsia patients with comorbidities in the inpatient unit of Majalengka Regional Hospital in 2024 was: the highest number patients were aged 46-55 years (24 patients, or 29%), and the highest number of patients were female (63 patients, or 78%). The most common single drug used for dyspepsia was ranitidine (14 cases, 87.50%). The most common two-drug combination was ranitidine and sucralfate (9 cases, 25.00%), and the most common three-drug combination was sucralfate + ranitidine + domperidone (12 cases, 37.50%). Drug interactions, based on severity, were classified as minor (32 cases, 96.97%), and moderate (1 case, 3.03%).